2020
DOI: 10.1111/1756-185x.14027
|View full text |Cite
|
Sign up to set email alerts
|

Association between Graves' disease and risk of incident systemic lupus erythematosus: A nationwide population‐based cohort study

Abstract: Objective Previous case reports have linked Graves' disease to incident systemic lupus erythematosus (SLE). It has also been reported that antithyroid drugs used to treat Graves' disease can induce SLE development. The purpose of this study was to investigate the risk of SLE in patients with Graves' disease. Methods A total of 8779 patients with Graves' disease and 8779 controls (without Graves' disease) matched by age, gender, index year, and Charlson Comorbidity Index (CCI) score were enrolled between 2000‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…20 SLE and GD frequently cooccur, with elevated incidence for both GD among SLE individuals and subsequent SLE development in GD patients. [21][22][23] This study confirmed a significant correlation between genetic variations strongly associated with SLE in the East Asian population and an elevated risk of GD occurrence through univariable MR analysis (OR 1.12). In other words, SLE patients in the East Asian population have a 12% higher risk of developing GD than those without SLE, providing supportive evidence for SLE as a causative factor for GD.…”
Section: Discussionsupporting
confidence: 76%
“…20 SLE and GD frequently cooccur, with elevated incidence for both GD among SLE individuals and subsequent SLE development in GD patients. [21][22][23] This study confirmed a significant correlation between genetic variations strongly associated with SLE in the East Asian population and an elevated risk of GD occurrence through univariable MR analysis (OR 1.12). In other words, SLE patients in the East Asian population have a 12% higher risk of developing GD than those without SLE, providing supportive evidence for SLE as a causative factor for GD.…”
Section: Discussionsupporting
confidence: 76%
“…The MR analysis indicated that patients with GD exhibit a 14% higher risk of developing RA, whereas those with RA have a 26% increased likelihood of developing GD. A cohort study of 8779 GD cases and 8779 controls in Taiwan showed that GD patients suffer an increased risk of SLE (hazard ratio [HR]: 5.45, 95%CI: 1.74-17.0) [32]. Based on our research, patients with GD have a higher chance of developing SLE as shown by a signi cant OR value of 1.31.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, research shows that GD is associated with a higher positive rate of incident SLE. Hyperthyroidism accelerates the basal metabolism and increases oxygen consumption and the production of reactive oxygen radicals, increasing oxidative stress leads to tissue peroxidation in the antioxidant defense system, and the immunological responses correlate with the disease activity and organ damage of SLE [15][16][17]. The role of cytokines and chemokines may be responsible for the inflammatory organdamaging response [18].…”
Section: Discussionmentioning
confidence: 99%